Pengembangan Media Pop Up Book Untuk Meningkatkan Kemampuan Membaca Permulaan Pada Anak Usia Dini - Febriani, Suryaning Ayu; Dwiyanti, Linda; Yulianto, Dema (Universitas Nusantara PGRI Kediri, 2023)
This study aims to improve the ability to read beginning by utilizing the development of media in the form of Pop up books. In this research, the type of research and development or commonly called R&D is used. The product validity data analysis technique uses the Aikens formula and in small group trials uses SPSS. From the analysis results can show the value of sig. ≥0.05 then it is said that the value of the questionnaire is declared valid. So it can be concluded that Pop up book media can improve early childhood reading skills.